Attitudes toward dating violence among college students in mainland China: an exploratory study - Anderson, Jared R.; Chen, Wen Chi; Johnson, Matthew D.; Lyon, Sarah E.; Lee, Chih-Yuan Steven; Zheng, Fuming; Ratcliffe, Gary C.; Peterson, F. Ryan (My University, 2013)
This study investigates attitudes toward psychological and physical dating violence among college students in mainland China (n = 245). The results of this study indicate that among our sample of college students in mainland China, men and women were relatively similar in their attitudes toward male perpetrated and female perpetrated physical dating violence and female perpetrated psychological dating violence. As has been found in previous research, men and women in our sample were more accepting of female perpetrated physical and psychological dating violence than male perpetrated physical and psychological dating violence. Finally, among several variables that predicted dating violence attitudes, shame emerged as a potentially important variable to include in future studies on dating violence in Chinese populations.
Keywords: China; College students; Dating violence; Predictors; Shame